Prevalence and Impact of Vertigo and Dizziness in Adults: A Hospital-Based Evaluation: Vertigo and Dizziness in Adults: A Hospital-Based Evaluation - Ikramullah, .; Hamza, Amir; Azam, Mohammad; Wahid, Abdul; Bari, Abdul (Pakistan Journal of Health Sciences, 2025)
Vertigo and dizziness are common complaints in adults, often affecting daily functioning and potentially linked to conditions such as hypertension, anxiety, and migraine, highlighting the need for more local data. Objectives: To determine the prevalence of vertigo and dizziness among adults in the local population, assess their impact on daily functioning using the Dizziness Handicap Inventory, and identify associated clinical and demographic risk factors, including hypertension, anxiety, and migraine. Methods: This cross-sectional study was conducted from January 2025 to June 2025 at Bolan Medical College, Quetta and Jhalawan Medical College, Khuzdar, enrolled 371 adults (≥18 years, residing in Quetta or Khuzdar for at least one continuous year, experiencing vertigo/dizziness, and providing consent) via simple random sampling. Data from interviews, records, and DHI assessed demographics, comorbidities, and symptom characteristics. Exclusions included psychiatric/CNS disorders. Analysis (SPSS v25) used descriptive statistics, parameter estimation, chi-square, and logistic regression (p<0.05 significant). Results: The mean age of patients was 42.3 ± 12.7 years. Male were 170 (45.8%) and female 201 (54.2%). Hypertension was found in 123 (33.2%), diabetes mellitus in 77 (20.8%), migraine in 62 (16.7%), and anxiety/depression in 93 (25.1%). The overall mean Dizziness Handicap Inventory score was 48.6 ± 18.4; male had 44.7 ± 17.2 and female 51.8 ± 18.9. Based on the Dizziness Handicap Inventory score, 104 (28.0%) had mild, 193 (52.0%) moderate, and 74 (19.9%) severe symptoms. Conclusions: Dizziness and vertigo are common in adults, often linked to hypertension, anxiety, and migraines. Early diagnosis, screening, and multidisciplinary management help reduce the burden and improve outcomes.